1974
DOI: 10.1073/pnas.71.2.325
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal and Molecular Structure of Ethyl Chlorophyllide a ·2H 2 O and Its Relationship to the Structure and Aggregation of Chlorophyll a

Abstract: Determination of the crystal structure of ethyl chlorophyllide a-2H20 by single crystal x-ray diffraction techniques has provided the first detailed molecular structural data available for a magnesium-containing derivative of chlorophyll. At the same time the aggregation observed in this structure serves as the basis for a model of chlorophyll aggregation in vitro and in vivo. The magnesium atom in ethyl chlorophyllide is displaced 0.4 A from the plane of the chlorin ring in the same direction as the methyl es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

1974
1974
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 13 publications
1
17
0
1
Order By: Relevance
“…Extensive work has permitted a relatively precise description of the associations assumed by chlorophyll in vitro [5,44,4649]. Particularly, IR and structural studies have demonstrated the prominent role played in these associations by: (i) the central magnesium atom, (ii) the ketonic and aldehyde carbonyls, and, (iii) in some instances, the carbonyl of the ester group on C,, [12,44,46,.…”
Section: Aggregation Of Chlorophyll In Nonpolar Solventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive work has permitted a relatively precise description of the associations assumed by chlorophyll in vitro [5,44,4649]. Particularly, IR and structural studies have demonstrated the prominent role played in these associations by: (i) the central magnesium atom, (ii) the ketonic and aldehyde carbonyls, and, (iii) in some instances, the carbonyl of the ester group on C,, [12,44,46,.…”
Section: Aggregation Of Chlorophyll In Nonpolar Solventsmentioning
confidence: 99%
“…Particularly, IR and structural studies have demonstrated the prominent role played in these associations by: (i) the central magnesium atom, (ii) the ketonic and aldehyde carbonyls, and, (iii) in some instances, the carbonyl of the ester group on C,, [12,44,46,. Fortunately, though probably not coincidentally, these same chlorophyll chemical groups yield observable contributions to RR spectra.…”
Section: Aggregation Of Chlorophyll In Nonpolar Solventsmentioning
confidence: 99%
“…Compound 1 shows hydrogen bonded chain structure, due to intermolecular hydrogen bonding between two porphyrin molecules via one lattice water molecule. 35 A close packed structure of compound 1 is shown in Figure S4 in Supplementary Information. In the crystal packing, neighbouring layers are stacked on each other forming a close packed polymer ( Figure S4).…”
Section: Crystal Structure Of Compoundmentioning
confidence: 99%
“…The stack could be arranged with all of the phytyl chains on one side, or the macrocycles could be arranged with phytyl chains on alternating sides of the stack. When the X-ray crystal structure of ethyl chlorophyllide a.2H20 was determined by Strouse (1973) some years later, the same macrocycle stacks with intercalated water coordinated to Mg, and hydrogen bonded to the keto C=O function of the adjacent macrocycle postulated for P740 from IR and EPR spectroscopy ) was present in the crystal structure. The most important consequence of our work on chlorophyll aggregates was the special pair concept for the primary electron donor in Photosystem I Katz 1968, Katz 1973b).…”
Section: Chlorella Vulgaris and Scenedesmus Obliquusmentioning
confidence: 99%